Caracterização da capacidade funcional de idosos institucionalizados e não institucionalizados - Assis, Reinaldo Braga de (2019)
Introduction: The progressive physiological decline that occurs due to the aging process and non-communicable chronic diseases are pointed out as possible primary causes that may affect the functional capacity among the elderly, especially the institutionalized ones that have characteristics of greater dependence and difficulty to perform tasks of everyday life. Objective: To characterize the functional capacity of institutionalized and non-institutionalized elderly. Methods: A cross-sectional, observational and descriptive study with (n = 60 elderly), of both sexes, aged 60 years or older, divided into 3 groups: GIIS (n = 15) - Sedentary Institutionalized Elderly, 30) - Active non-institutionalized elderly and GINIS (n = 15) - Non-institutionalized elderly sedentary. Data were collected on the characterization of the sample (age, BMI and waist /hip ratio), and functional abilities (Katz daily life activity index, Lawton daily life activity scale, Berg balance scale, Timed test Up and Go (TUG), sit-and-reach test (wells bench) and sit-up test in the chair). The normality of the data was verified by the Shapiro-Wilk test. Data with normal distribution are presented in mean and standard deviation and data with non-normal distribution in median and interquartile range. For the analysis of the differences between the groups, the Anova One-Way Test with post hoc Tukey and the Kruskal Wallis Test with Mann-Whitney Test and Bonferroni correction were used. Data were analyzed in the statistical program SPSS version 20, adopting the level of significance of 5%. Results: The GIIS showed statistically significant characteristics of older age, lower BMI, greater risk of cardiovascular disease, higher score in the Katz index and longer time to perform the TUG test, lower score in the Lawton scale and Berg scale and lower number of repetitions in the sit and stand test of the chair, as well as lower articular range of motion of the upper and lower limbs, compared to GINIA and GINIS. Conclusion: Institutionalized elderly individuals have characteristics of older age, lower BMI and higher risk of cardiovascular disease, greater dependence for ADL and AIVD, lower balance, lower muscle strength and resistance of lower limbs, lower articular range of motion of upper and lower limbs, and greater risk of falls in relation to the non-institutionalized elderly